A new art from emerging markets - Robertson, Iain (Iain Alexander) (Lund Humphries, 2011)
A New Art From Emerging Markets sets out to introduce and examine three types of emerging market for contemporary art: the very recently established, the maturing and the mature. In temporal terms, the youngest are no more than five years old; the maturing, fifteen years old; and the mature up to twenty-five years old.